Introduction to Juries and Mixed Tribunals across the Globe: New Developments, Common Challenges and Future Directions - Nancy S. Marder; Valerie P. Hans (Oñati Socio-Legal Series)
The introduction to the special issue describes the goals of the conference on Juries and Mixed Tribunals across the Globe, and identifies themes that emerged as jury scholars from all over the world examined different forms of lay participation in legal decision-making. The introduction focuses on common challenges that different systems of lay participation face, including the selection of impartial fact finders and the presentation of complex cases to lay citizens. The introduction and special issue articles also highlight new developments and innovative practices to address these challenges, including some tools, like decision trees, that remain highly controversial. The introduction closes by emphasizing the enduring political importance of citizen participation in law.